2016
DOI: 10.1002/rcm.7677
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of gaseous barium cerate studied by Knudsen effusion mass spectrometry

Abstract: The stability of BaCeO3 gaseous species was confirmed by high-temperature mass spectrometry. Gas-phase reactions involving gaseous barium and cerium oxides with gaseous barium cerate were studied. The enthalpies of the formation reactions of gaseous barium cerate from gaseous BaO and CeO2 were evaluated theoretically and the obtained values were in agreement with the experimental ones. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The partial pressures of the gaseous species over the CeO 2 –SiO 2 –X systems calculated by the ion current comparison method (Equation ) are listed in Tables S1 and S2 (supporting information). The partial pressures were calculated by taking into account the fragmentation contribution, CeO + (CeO 2 ), XO 2 + (XO 3 ), as described in detail in the literature . The partial pressures of the cerium molybdates and tungstates are small (10 −2 to 10 −4 Pa) in comparison with those of the cerium and molybdenum (tungsten) oxides and differ by approximately three orders of magnitude.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The partial pressures of the gaseous species over the CeO 2 –SiO 2 –X systems calculated by the ion current comparison method (Equation ) are listed in Tables S1 and S2 (supporting information). The partial pressures were calculated by taking into account the fragmentation contribution, CeO + (CeO 2 ), XO 2 + (XO 3 ), as described in detail in the literature . The partial pressures of the cerium molybdates and tungstates are small (10 −2 to 10 −4 Pa) in comparison with those of the cerium and molybdenum (tungsten) oxides and differ by approximately three orders of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…The average values of the enthalpies of reactions 5–13 were recalculated to the temperature 298 K. The thermodynamic functions of the gaseous oxide were taken from the literature . The thermodynamic functions of CeWO 3 , CeMoO 4 , CeWO 4 , CeMoO 5 , CeWO 5 and CeMo 2 O 7 molecules were calculated by statistical thermodynamics in a “rigid rotor‐harmonic oscillator” approximation on the basis of the structures and vibrational frequencies obtained by several ab initio and DFT quantum chemistry methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxyacid salts can be thought of as products of the reaction between acidic and basic oxides. It has been established that the CeO and CeO 2 molecules are the significant vapor species in equilibrium with solid cerium dioxide . To synthesize gaseous cerium molybdates and tungstates, CeO 2 was evaporated from molybdenum or tungsten effusion cells.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 Reasonable data agreement was obtained when the value σ(VO 2 )/σ(VO) = 1.14 (Mann 3 , additivity rule) was replaced by the factor 0.33. 12,13 Earlier, 15 we found that in the isocation series of gaseous oxyacid salts the atomization enthalpy of gaseous salts was linearly dependent on the atomization enthalpy of the gaseous anion-forming oxides, with the actual dependence being represented by Equation 23: This dependence for the cerium isocation series is depicted in Table 3.…”
mentioning
confidence: 84%